Thai clinicians’ attitudes toward antimicrobial stewardship programs - Nantanit Sutthiruk (2019)
© 2018 Association for Professionals in Infection Control and Epidemiology, Inc. Background: Effective hospital-wide antimicrobial stewardship (AMS) programs need multidisciplinary engagement; however, clinicians’ attitudes have not been investigated in Thailand where AMS is in early development. The aim of this study was to explore Thai clinicians’ (doctors, nurses, and pharmacists) perceptions and attitudes toward AMS. Methods: A paper-based survey was distributed in a 1,000-bed university hospital in Bangkok, Thailand, between November 9, 2015, and December 21, 2015. A total of 1,087 clinicians participated: 392 doctors, 613 nurses, and 82 pharmacists. Results: Most participants agreed that improving antimicrobial prescribing would decrease antimicrobial resistance (AMR) and should be a priority of hospital policy. Doctors were less likely to agree with policies that limit antimicrobial prescribing (P <.001) than nurses or pharmacists, and were less likely to be interested in participating in AMS education than other clinicians (P <.001). Pharmacists indicated higher agreement with the statement, recommending that a specialist team provide individualized antimicrobial prescribing advice (P <.01) and that feedback improves antimicrobial selection (P <.001). Nurses were less likely to agree that community antibiotic use (P <.001) or patient pressure for antibiotics contribute to AMR (P <.001). Conclusions: AMS programs are vital to improving antimicrobial use by clinicians. Understanding clinicians’ attitudes and perceptions related to AMS is important to ensure that AMS programs developed address areas relevant to local clinical needs.